Achieving adherence to positive airway pressure in commercial drivers using an employer-mandated remote management programme - Elizabeth Kneeland; Nadia Ali; David G. Maislin; Yoon Hee Chang; Joyce Epelboim; Brendan T. Keenan; Allan I. Pack (ERJ Open Research)
Background Obstructive sleep apnoea (OSA) is common in commercial drivers, and associated with increased risk of crashes if untreated, making diagnosis and effective treatment crucial in this population. Study design and methods This is a retrospective summary of a clinical programme based on telemedicine and remote treatment monitoring developed with a national trucking company to screen new hires in the USA for OSA and implement positive airway pressure (PAP) management. New hires were informed of the programme and consented as part of their employment. Drivers who did not comply with the evaluation or with PAP after diagnosis were removed from driving commercial vehicles by the company or did not pursue further employment. Results A total of 975 drivers were enrolled. Among screened drivers, 35.5% were cleared without a sleep study, 15.0% were cleared following a sleep study (apnoea–hypopnoea index (AHI) <5 events·h−1), 22.1% had mild OSA (AHI 5–15) and 27.4% had moderate–severe OSA (AHI ≥15). Those with moderate–severe OSA were more obese (body mass index 36.2±6.3 kg·m−2) and had more comorbidities. Of 269 drivers starting PAP, 160 (59.5%) maintained participation in a care management programme, 80 (29.7%) resigned or were terminated, 23 (8.6%) were cleared to discontinue PAP and six (2.2%) were complex cases requiring transfer of care. Illustrating effectiveness, those that maintained participation had excellent PAP adherence (5.27±1.61 h·night−1; 88.5±12.9% days used; 79.7±17.7% days used ≥4 h). Interpretation Remote assessment of OSA and PAP management in commercial drivers is feasible and effective. This approach has wide-ranging applications, particularly in populations and areas with a lack of sleep medicine providers.